2004
DOI: 10.1063/1.1827330
|View full text |Cite
|
Sign up to set email alerts
|

Applied field Mössbauer study of shape anisotropy in Fe nanowire arrays

Abstract: In order to investigate the magnetic anisotropy of Fe nanowire arrays from microscopic point of view, Fe57 Mössbauer spectra were measured at various magnetic fields along and perpendicular to the nanowire axis, respectively. On the basis of the absorption intensities of the second and the fifth lines of sextet, the orientation of Fe magnetic moments can be detected. It was found that the shape anisotropy dominates the overall magnetic anisotropy in the Fe nanowires. Furthermore, the longitudinal and transvers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…In addition, the coercive field at 5 K parallel to the nanowire axes is in agreement with the chain spheres of the symmetric fanning mechanism HðsyÞ ¼ M s ð6K n À 4L n Þ=6 ¼ 3:15 kOe, where M s ¼ 1950 emu/cc is the saturation magnetization for bulk Fe 55 Co 45 alloy [22,23]. On the other hand, when the field is perpendicular to the wire axes the transverse coercivity being 0.522 kOe observed in our result should mainly come from the magnetocrystalline anisotropy [20]. Fig.…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the coercive field at 5 K parallel to the nanowire axes is in agreement with the chain spheres of the symmetric fanning mechanism HðsyÞ ¼ M s ð6K n À 4L n Þ=6 ¼ 3:15 kOe, where M s ¼ 1950 emu/cc is the saturation magnetization for bulk Fe 55 Co 45 alloy [22,23]. On the other hand, when the field is perpendicular to the wire axes the transverse coercivity being 0.522 kOe observed in our result should mainly come from the magnetocrystalline anisotropy [20]. Fig.…”
Section: Methodssupporting
confidence: 90%
“…Similar shapes of magnetic hysteresis loops are measured in the temperature ranging from 5 to 300 K. These characteristics illustrate that the nanowire arrays have easy magnetization direction along the wire axes due to the strong shape anisotropy. The applied Mo¨ssbauer spectroscopy for Fe nanowire arrays has proved that the shape anisotropy dominates the overall magnetic anisotropy in the nanowire arrays [20]. Although the competition of the dipolar interaction and shape anisotropy determined the easy direction parallel or perpendicular to the wire axes [21], but for our nanowire arrays the main anisotropy origin is the shape anisotropy and the easy direction axes are along the wire axes.…”
Section: Methodsmentioning
confidence: 98%
“…Both mechanisms have been examined numerically for different length of nanoparticles chains [30,32]. They have been also used for describing experimental results [3334]. According to theoretical calculations and experimental results shown in different publications, the ”fanning mechanism” yields lower coercivity values than the ”parallel rotation mechanism”.…”
Section: Resultsmentioning
confidence: 99%
“…A curling model and a chain-of-sphere model with symmetric fanning mechanism have been usually used to interpret the hysteresis behavior of magnetic nanowire arrays [8,24]. In terms of these two models, the coercivity will decrease with the diameter of nanowire.…”
Section: Room-temperature Magnetic Propertymentioning
confidence: 99%
“…So far, a lot of metal, alloy and multilayer magnetic nanowires based on AAO templates have been successfully fabricated. Some unique magnetic properties, such as anisotropic magnetization, GMR effect and magnetooptical property have been widely investigated [8][9][10][11]. It was found that these properties strongly depend on the diameter and the aspect ratio of nanowires.…”
Section: Introductionmentioning
confidence: 99%